Genetic characterisation of autochthonous sweet cherry genotypes (Prunus avium L.) using SSR markers - Krmpot, Tanja; Rados, Ljubomir; Vokurka, Ales (Genetika (Beograd), 2020)
The autochthonous local genotypes of sweet cherries, which represent a very important genetic potential for future breeding programs. Understanding of the molecular basis biodiversity is one of the most important factors for the proper conservation, management and use of plant genetic resources. This paper investigate the genetic variability of 14 genotypes of sweet cherries using 26 SSR markers. The study included eight autochthonous genotypes of sweet cherry taken from four different location and six virus-free reference varieties of sweet cherry. The average genetic distance between them was 0.43. The number of alleles per locus ranged from two to eight. The minimum number of two alleles of polymorphic loci showed EMPa003 and EMPa002, while the highest number of eight loci alleles had PceGA34 and UDP97-402. Results of genetic analysis that were done show that between autochthonous genotypes of sweet cherries ?Biljur-Bjelica?, ?Barevka? and ?Aslamka? (Kriskovci) there was no difference, it is to have the same genetic profil, which indicates that is the synonym, it is the same identity group. Also the autochthonous genotype ?Crveni Hrust? and ?Nordwunder? cultivar had the same SSR profile on microsatellite loci tested. The remaining autochthonous genotypes of sweet cherry had a unique genetic profile. nema